Factors affecting urinary continence and sexual potency recovery after robotic-assisted radical prostatectomy - Neumaier, Mark Fernando; Segall Júnior, Carlos Henrique; Hisano, Marcelo; Rocha, Flávio Eduardo Trigo; Arap, Sami; Arap, Marco A. (International Brazilian Journal of Urology, 2019)
Robot-assisted radical prostatectomy (RARP) is the most recent surgical technique for localized prostate cancer. The Da Vinci (Intuitive Surgical, Sunnyvale, CA) system was first introduced in Brazil in 2008, with a fast growing number of surgeries performed each year. Our primary endpoint is to analyze possible predictors of functional outcomes, related to patient and tumor features. As secondary endpoint, describe functional outcomes (urinary continence and sexual potency) from RARP performed in the Sírio-Libanês Hospital (SLH), a private institution, in São Paulo, from April 2008 to December 2015. Data from 104 consecutive patients operated by two surgeons from the SLH (MA and SA) between 2008 and 2015, with a minimum 12 months follow-up, were collected. Patient features (age, body mass index - BMI, PSA, date of surgery and sexual function), tumor features (tumor stage, Gleason and surgical margins) and followup data (time to reach urinary continence and sexual potency) were the variables collected at 1, 3, 6 and 12 month and every 6 months thereafter. Continence was defined as the use of no pad on medical interview and sexual potency defined as the capability for vaginal penetration with or without fosphodiesterase type 5 inhibitors. Mean age was 60 years old and mean BMI was 28.45 kg/m2. BMI >30kg/m2 (p<0.001) and age (p=0.011) were significant predictors for worse sexual potency after surgery. After 1, 3, 6 and 12 months, 20.7%, 45.7%, 60.9% and 71.8% from patients were potent, respectively. The urinary continence was reached in 36.5%, 80.3%, 88.6% and 92.8% after 1, 3, 6 and 12 months, respectively. Until the end of the study, only one patient was incontinent and 20.7% were impotent. Age was a predictor of urinary and erectile function recovery in 12 months. BMI was significant factor for potency recovery. We obtained in a private hospital good functional results after 12 months of follow-up.